KONSEP KESALINGAN MASYARAKAT ADAT KASEPUHAN CIPTAGELAR - Aini, Siti Noor (Jurnal Ilmiah Citra Ilmu, 2022)
Kasepuhan Ciptagelar is an indigenous community living in the Halimun Salak mountain, Sukabumi, West Java. The Ciptagelar community cannot be separated from ancestral customs that have become a part of daily life. Planting rice is part of ancestral customs that must be done by the Ciptagelar community. The process of planting rice involves many rituals involving women and men. In routine activities and rituals throughout the rice garden season, the roles of women and men are mutually supportive. This is a form of lonely relations that exist within the Ciptagelar indigenous community. How was the concept of the alienation of the Cariptagelar community formed? The purpose of this study is to explore aspects that become the occurrence of the concept of loneliness in the Ciptagelar community. The method used in the research is descriptive-qualitative with a participatory paradigm. The results of this study found new knowledge about aspects of the concept of loneliness in the Ciptagelar community.